From RLP to SLP: Two Different Approaches to Landscape Planning - Federica Isola; Cheti Pira (TeMA: Journal of Land Use, Mobility and Environment, 2014)
The concepts of governance and sustainable development are concepts related to complex systems and processes, in terms of problems and implications, with a variety of people involved in different ways and whose number has increased over time. In the processes of regional governance, the concept of sustainability interacts with the environment and to the territory. Since 2006, year of approval of its Regional Landscape Plan (RLP), the Region of Sardinia, has been experiencing a new era of regional governance characterisedcharacterized by a new understanding of environmental resources; and by a different relational approach among regional government bodies, as well as between them and local communities. In 2009 began the revision phase of the plan recently concluded with the approval of the Sardinia Landscape Plan (SLP). This paper will highlight a comparison between RLP and SLP focusing on three aspects: i) the concept of protection and safeguarding of the territory; ii) the institutional governance; iii) the application of the Strategic Environmental Assessment.